Blockchain-Based Electronic Health Records: Revolutionizing healthcare in Malaysia - Fariha Anjum Hira; Haliyana Khalid; Alam Md Moshiul (ACHSM, 2024)
Introduction: Despite the government's continuous efforts since the 1990s, the public healthcare sector of Malaysia still faces issues related to system deployment and technology adoption. As a result, the nationwide health information exchange remains as not fully established, hampering the Malaysian aspirations of health service provision for citizens. The government long to establish health information exchange, enabling blockchain technology-based applications. This paper aims to review the government's digitalization initiatives and describe the provision of blockchain Electronic Health Records for healthcare services in Malaysia. Methodology: A review of the scholarly databases Scopus, Web of Science, and Google Scholar, along with the grey literature from the Malaysian government, was conducted. In addition, health-related government websites have been searched for information until the end of March 2023. Results: There were 55 documents yielded from the database, and a grey literature search was retained for content analysis. Discussion: The major barrier that could push back governments' efforts is user resistance, particularly from medical professionals. Besides, Regulatory reform is needed to facilitate blockchain provision for healthcare data management. Technical issues directly associated with the system and vendor are worth addressing. Conclusion: Malaysia has a progressive vision towards healthcare digitalization aimed at 2030. To be able to successfully achieve this target then it is essential to implement appropriate strategies. User readiness assessment calls for research, while system-related issues regarding; hardware, software, and vendor needs to be properly planned. Patients' ownership of medical data is to be allowed by law. Currently this information strictly belongs to hospitals and health partitioners therefore data management is physician centric.